Development of Tourism Accessibility for Ider Galengan in Tambong Village through the Construction of a Knockdown Bridge Based on Green Materials to Enhance Tourist Attraction - Wiryasuta, I Ketut Hendra; Amin, M. Shofiul; Fahmi Dian Sukma, Imam; Ariyanto Sandi, Enes; Kanom, Kanom (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
The Ider Galengan Educational Tourism Area in Tambong Village still lacks adequate infrastructure, particularly a pedestrian bridge that is no longer safe for visitors. This condition reduces comfort and the attractiveness of the tourism site. This community service program aims to construct a knockdown bridge made from green materials to improve site accessibility and to increase community knowledge through training on bridge construction and sustainable tourism concepts. The program included site surveys, bridge design, component fabrication, on-site installation, and training involving 31 participants. Knowledge improvement was evaluated using pretest–posttest analysis through normality tests, homogeneity tests, N-Gain score, and the Paired Sample t-test. The results show an N-Gain value of 0.70, categorized as high effectiveness, and a significant difference between pretest and posttest scores. Satisfaction evaluation from 8 partner respondents indicated an 86% satisfaction level. Overall, this program successfully improved tourism accessibility and enhanced community understanding of sustainable construction.